Potential of Acid-Activated Bentonite and SO3H-Functionalized MWCNTs for Biodiesel Production From Residual Olive Oil Under Biorefinery Scheme - Rahimzadeh, Hadi; Tabatabaei, Meisam; Aghbashlo, Mortaza; Panahi, Hamed Kazemi Shariat; Rashidi, Alimorad; Goli, Sayed Amir Hossein; Mostafaei, Mostafa; Ardjmand, Mehdi; Nizami, Abdul-Sattar (Frontiers in Energy Research, 2018)
Application of acid-activated bentonite and SO3H-functionlized multiwall carbon nanotubes (SO3H-MWCNTs) for lowering free fatty acids (FFAs) content of low-quality residual olive oil, prior to alkali-catalyzed transesterification was investigated. The used bentonite was first characterized by Scanning Electron Microscopy (SEM), Inductively Coupled Plasma mass spectrometry (ICP-MS), and X-ray fluorescence (XRF), and was subsequently activated by different concentrations of H2SO4 (3, 5, and 10 N). Specific surface area of the original bentonite was measured by Brunauer, Emmett, and Teller (BET) method at 45 m2/g and was best improved after 5 N-acid activation (95–98°C, 2 h) reaching 68 m2/g. MWCNTs was synthesized through methane decomposition (Co-Mo/MgO catalyst, 900°C) during the chemical vapor deposition (CVD) process. After two acid-purification (HCl, HNO3) and two deionized-water-neutralization steps, SO3H was grafted on MWCNTs (concentrated H2SO4, 110°C for 3 h) and again neutralized with deionized water and then dried. The synthesized SO3H-MWCNTs were analyzed using Fourier-Transform Infrared Spectroscopy (FTIR) and Transmission Electron Microscopy (TEM). The activated bentonite and SO3H-MWCNTs were utilized (5 wt.% and 3 wt.%, respectively), as solid catalysts in esterification reaction (62°C, 450 rpm; 15:1 and 12:1 methanol-to-oil molar ratio, 27 h and 8 h, respectively), to convert FFAs to their corresponding methyl esters. The results obtained revealed an FFA to methyl ester conversion of about 67% for the activated bentonite and 65% for the SO3H-MWCNTs. More specifically, the acid value of the residual olive oil was decreased significantly from 2.5 to 0.85 and 0.89 mg KOH/g using activated bentonite and SO3H-MWCNTs, respectively. The total FFAs in the residual olive oil after esterification was below 0.5%, which was appropriate for efficient alkaline-transesterification reaction. Both catalysts can effectively pretreat low-quality oil feedstock for sustainable biodiesel production under a biorefinery scheme. Overall, the acid-activate bentonite was found more convenient, cost-effective, and environment-friendly than the SO3H-MWCNTs.